HUBUNGAN PEMBERIAN ASI EKSLUSIF DAN PENGETAHUAN IBU DENGAN KEJADIAN WASTING - Halimah, Siti; Septia, Qori Armiza; Zalni, Rummy Islami; Luthfiyah, Ummu; Aristi, Tiffany Atia; Wilda, Tri Oktavia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Wasting is a condition in which young children lose very little weight, or are below the normal range caused by insufficient nutritional needs of young people. Wasting can also be caused by knowledge in not giving exclusive milk to the young, and incorrect feeding. The purpose of this research is to find out the relationship between exclusive breastfeeding and mother's knowledge of the event Wasting on the news in the area of work puskesmas nursing sidomulyo. The study was conducted from May to June 2024 with a type of analytical study with a cross sectional survey design, total samples of 44 respondents. Analysis of exclusive breast milk using Chi[1]square test results P value 0,000 (p<0,05) means there is a significant relationship between exclusive milk and Wasting event. Based on the analysis of mother's knowledge of Wasting events using the chi-scuare test obtained a P value result of 0.023 (p <0.05) meaning there is significant relationship of mother knowledge with Wasting Event. The researchers' advice is for families and the community to understand and pay attention to the symptoms associated with wasting on news.Keywords: Wasting Events, ASI Exclusive, Knowledge